Influência dos efeitos antrópicos, edáficos e vegetacionais sobre a estrutura populacional de Attalea pindobassu Bondar – babaçu, na caatinga - Lima, Bárbara Alves de Oliveira (2024)
The emergence of anthropic habitats negatively affects biodiversity and ecosystem services. In these habitats, the exploitation of non-timber forest products has been intensified. Babassu (Attalea pindobassu Bondar), a palm tree endemic to the North of Chapada Diamantina, Bahia, is a species of high extractive use and socioeconomic importance. The region has varied environments modified through the removal of vegetation cover, which poses a risk to native species. The study aimed to evaluate the structural characteristics of 14 populations of A. pindobassu in areas with different levels of disturbance. For populations in areas of native vegetation, three to six plots of 30x15 m were established, with a subplot of 7x7 m for sampling regenerants. In pasture areas or agricultural crop plantations, three to six 50x50 m plots were established, with a 5x50 m subplot for regenerants. Individuals were classified into five ontogenetic stages: seedling, infant, young, immature adult and reproductive adult. Quantitative measurements were collected to classify ontogenetic stages based on leaf type, presence/absence of stipe and presence/absence of reproductive structure. In general, 92.8% of the populations evaluated had records of regenerating individuals. Regarding the distribution of size classes, most populations showed positive asymmetry, where it was possible to observe low levels of anthropogenic actions. Regarding the distribution of height classes, 93% of the populations achieved adjustment to the Inverted-J curve, demonstrating that there is low interference in the natural regeneration process. It was possible to observe that the influence of anthropogenic factors affected the density of individuals more than edaphic factors. For all ontogenetic stages, the density of individuals was negatively affected by human actions, suchas agriculture, cattle breeding, fruit harvesting and wood extraction. Therefore, through the study it was possible to observe how activities resulting from human action can affect the natural life cycle of an endemic plant species. The creation of conservation plans and implementation of management practices are crucial for the conservation of the species.